A praxeological review of concept-sequence and series: Comparing Malaysia and Indonesia textbooks - Kusharyadi, Rahmat; Fatimah, Siti; Kusnandi, Kusnandi (Jurnal Elemen, 2024)
Malaysia, through its curriculum, has implemented mathematics textbooks as the main source. However, not all concepts can be offered to a country. This research aims to analyse the comparison between Indonesian and Malaysian textbooks from a praxeological perspective . The data used is only on the topic of sequences and series. This qualitative research adopts a hermeneutic phenomenological approach, serving as an alternative method. In the context of the Indonesian version of didactic design, this study represents research conducted during the prospective stage of the entire research series. The results of the research show that in the praxis block, there are similarities in the presentation of Indonesian and Malaysian textbooks in introducing the topic of sequences and series. The difference is that in Indonesian mathematics textbooks there are 2 themes, while in Malaysia there is only 1 theme. The design in Malaysian textbooks is more in-depth and comprehensive, and the learning trajectory is arranged more systematically so that Malaysian textbooks allow for no gaps between the types of T used. The use of Malaysian textbooks has the potential to build complete knowledge, so the potential for students to have difficulties will be smaller.